Revision of the central Mediterranean xerothermic cliff vegetation. Issue 3 (22nd July 2018) - Terzi, Massimo; Jasprica, Nenad; Caković, Danka; Di Pietro, Romeo
Abstract: Questions: What are the syntaxonomic and synchorological patterns of the xerothermic chasmophytic vegetation in the central part of the Mediterranean Basin? What are the diagnostic species of the high‐rank syntaxa of Asplenietalia glandulosi, Onosmetalia frutescentis and Centaureo dalmaticae‐Campanuletalia pyramidalis ? Location: Mediterranean coastal and subcoastal areas of southern France, Italy, Malta, Slovenia, Croatia, Bosnia and Herzegovina, Montenegro, Albania and of mainland Greece. Methods: The data set of 1, 261 published relevés was analysed using hierarchical clustering (Flexible Beta method), involving a series of data transformations. Indicator species analysis was used to select the best dendrogram solution and identify diagnostic taxa of the main clusters. The dendrogram was interpreted from a syntaxonomic point of view, using nomenclatural type relevés as a basis. The NMDS ordination was performed in order to visualize the floristic relationships among associations and high‐rank syntaxa. MRPP was used to test for differences among alliances. Results: The classification revealed four main clusters of relevés representing the chasmophytic vegetation of southern France, Sardinia and the northwestern part of Italy ( Asplenienalia glandulosi / Asplenietalia glandulosi ), the southwestern part of Italy and Malta ( Tinguarrenalia siculae / Asplenietalia glandulosi ), the Adriatic Basin area ( Centaureo dalmaticae‐Campanuletalia pyramidalis ) and the southern Balkans ( Onosmetalia frutescentis ). The NMDS ordination confirmed the overall pattern, while MRPP showed significant differences among the alliances of the above‐mentioned orders and suborders. The lists of diagnostic taxa of the high‐rank syntaxa were revised according to a supra‐national perspective. Conclusions: The new syntaxonomic scheme provides a comprehensive overview of the chasmophytic vegetation of the central part of the Mediterranean Basin. This scheme mostly matches the recently published EuroVegChecklist, but also exhibits important novelties concerning the syntaxonomic position of some alliances ( Dianthion rupicolae, Centaureion pentadactyli, Arenarion bertolonii and Caro‐Aurinion ), and the floristic and chorological relationships among high‐rank syntaxa, with new revised sets of diagnostic taxa. This revision might be useful for further small‐scale phytosociological studies. Abstract : A syntaxonomic revision of the xerothermic cliff vegetation of the central Mediterranean Basin is here presented. Syntaxonomic and synchorological relationships among the orders Asplenietalia glandulosi, Centaureo dalmaticae‐Campanuletalia pyramidalis, and Onosmetalia frutescentis were identified and discussed. The diagnostic species of the high‐rank syntaxa (orders and alliances) were identified under a supranational perspective through statistical processing of phytosociological data.